2018
DOI: 10.1159/000487310
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Sewn versus Stapled Closure of Loop Ileostomy: A Meta-Analysis

Abstract: Background: Individual trials comparing hand-sewn with stapled closure of loop ileostomy show different outcomes due to lack of statistical power. A systematic review, with a pooled analysis of results, might provide a more definitive answer. This review aimed to compare hand-sewn with stapled anastomotic technique for closure of a loop ileostomy and looked at the effect of bowel resection on the complication rates. Methodology: Relevant studies were identified from MEDLINE, EMBASE and the Cochrane database. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
2
25
5
2
Order By: Relevance
“…In this context, the additional operative cost of a stapling device has been justified based on a reduction in operating time or length of stay [22][23][24]. A consistent finding from the randomised controlled trials comparing stapled and hand-sewn ileostomy closures is the significantly shorter operating time for stapled ileostomy closures, with the benefit ranging from 4 to 24 minutes [23][24][25][26]. The technique used impacts upon the magnitude of this benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the additional operative cost of a stapling device has been justified based on a reduction in operating time or length of stay [22][23][24]. A consistent finding from the randomised controlled trials comparing stapled and hand-sewn ileostomy closures is the significantly shorter operating time for stapled ileostomy closures, with the benefit ranging from 4 to 24 minutes [23][24][25][26]. The technique used impacts upon the magnitude of this benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis done by Madani et al shown that the anastomotic leak rate was 2.93% (55/1,877) in the HA group and 2.08% (25/1,202) in the SA group with p=0.52. 6 We can say that there is no superiority in terms of having less anastomotic leak between these two methods and further study with large group of patient is required to strengthen this analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the surgical techniques, a recently published meta-analysis (17) compared the hand-sewn with stapled anastomotic technique for closure of the loop ileostomy and found no significant difference in the rate of anastomotic leakage between the two options, but the rate of small-bowel obstruction was higher in the handsewn group (17). Zhou, et al found that the length of hospital stay was shorter in the hand-sewn anastomoses than in the stapled anastomoses' group (10).…”
Section: Discussionmentioning
confidence: 99%